Diagnostic accuracy and microbial profiles of tuberculous pleurisy: a comparative study of metagenomic next generation sequencing and GeneXpert Mycobacterium tuberculosis - Huang, Fengxiang; Wang, Haoran; Qiao, Ruiping; Peng, Qiang; Zhao, Chang; Miao, Lijun (Frontiers in Cellular and Infection Microbiology, 2023)
There is a clinical challenge in diagnosing tuberculous pleurisy accurately and promptly, highlighting the urgent need for a rapid and sensitive diagnostic method.This study aimed to evaluate the diagnostic accuracy of metagenomic next-generation sequencing (mNGS) and GeneXpert Mycobacterium tuberculosis (MTB) for identifying tuberculous pleurisy and analyzing the microbial profiles of both tuberculous and non-tuberculous pleural effusions. The study enrolled 31 patients with suspected tuberculous pleurisy, of which 15 were confirmed to have tuberculous pleurisy and subsequently allocated to the tuberculous pleurisy group (TP group), while the remaining 16 individuals were assigned to the non-tuberculous pleurisy group (NTP group). mNGS and GeneXpert MTB were performed on pleural effusion samples, and the diagnostic accuracy of both tests was compared. We employed established formulas to compute crucial indicators, including sensitivity, specificity, missed diagnosis rate, misdiagnosed rate, positive predictive value (PPV), and negative predictive value (NPV). The results showed that both tests had high specificity (100%) and positive predictive value (100%) for detecting tuberculous pleurisy, along with comparable sensitivity (46.67% for mNGS and 40.0% for GeneXpert MTB). Further analysis of the combined efficacy of mNGS and GeneXpert MTB showed that the combined test had a sensitivity of 66.67% and a specificity of 100%. mNGS analysis revealed that MTB was detected in 7 out of 15 patients with tuberculous pleural effusions, while non-tuberculous pleural effusions were associated with a diverse range of microbial genera and species. The most frequently detected genera at the microbial genus level in the NTP group were Microbacterium spp. (6/16), Prevotella spp. (5/16), and Campylobacter spp. (5/16).These findings suggest that mNGS and GeneXpert MTB are useful diagnostic tools for identifying patients with tuberculous pleurisy, and mNGS can provide valuable insights into the microbial profiles of both tuberculous and non-tuberculous pleural effusions.